Reactualization of Muhammadiyah's Educational Philosophy in the Contemporary Era - Sadaruddin, Maulida Ade Suryani; Maksum, M. Nur Rochim; Salim, Hakimuddin (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This research aims to understand the philosophy of Muhammadiyah education, the challenges it faces, and efforts to reactualize the philosophy of Muhammadiyah education in addressing educational challenges in the contemporary era. Methodology: This study employs a qualitative approach, incorporating literature reviews. Results: The results of this study demonstrate that the principles of Muhammadiyah's educational philosophy comprise ontological principles, including the value of monotheism, epistemological principles that integrate revelation with reason, and axiological principles relevant to the goals and values of Muhammadiyah education. Applications/Originality/Value: Reactualization efforts that can be carried out in Muhammadiyah education include strengthening transformative and profound integration-interconnections, responding to the digital revolution by focusing on critical digital literacy, and pedagogical reactualization by prioritizing a student-centered learning approach.